Genetic Determinants of Clarithromycin and Fluoroquinolones Resistance in Helicobacter pylori in Serbia - Dusan Kekic; Milos Jovicevic; Jovana Kabic; Iva Lolic; Ina Gajic; Stefan Stojkovic; Lazar Ranin; Tomica Milosavljevic; Natasa Opavski; Ivan Rankovic; Vladimir Milivojevic (MDPI AG, 2024)
Background/Objectives: Stomach infections by Helicobacter pylori can cause acute or chronic gastritis, peptic ulcers, and gastric cancer. The rise in antibiotic resistance is a significant health issue highlighted by the World Health Organization. The increasing number of treatment failures underscores the necessity for antibiotic susceptibility testing (AST). The study aimed to investigate the current prevalence and resistance to fluoroquinolones and clarithromycin with their detected mutations. Methods: Stomach biopsies from symptomatic patients were subjected to molecular testing by GenoType Helico DR kit (Hain Lifescience GmbH, Nehren, Germany). Results: Positive findings on the presence of H. pylori were detected in 42.4% of symptomatic patients, with the significant majority of patients (69%) having previously failed treatments. The resistance rates to fluoroquinolones and clarithromycin were 53.9% and 58.5%, respectively, with significantly higher rates in secondary resistant strains. The main resistance markers in fluoroquinolones and clarithromycin were N87K (27.4%) and A2147G (78.6%), respectively. Hetero-resistance or mixed genotypes were detected in over 20% of tested patients. During the study period, a significant increase in trends in both fluoroquinolones and clarithromycin resistance rates was observed. Conclusions: Results indicate the need for the implementation of the latest Maastricht VI Consensus recommendations for both AST whenever possible and the use of tailored guided therapy options due to high resistance rates and possible treatment failures. The GenoType Helico DR kit is a useful tool for AST, especially in cases of mixed H. pylori genotypes.